Standarisasi Mutu Musyrif Dalam Menjamin Kualitas Pendidikan di Ma’had Aly Nurul Jadid - Hikmatul Hidayah; Mawadatur Rohmah; Hefniy Hefniy (AFKARINA: Jurnal Pendidikan Agama Islam, 2021)
This research is a qualitative research that aims to find out and evaluate how big the quality standards of musyrif and musyrifah services are as well as the quality of these musyrif musyrifahs in the academic process that exists at Ma'had Aly Nurul Jadid. Where musyrif musyrifah here is the manager and activator who accompanies, helps, motivates, conditions and directs students at Ma'had Aly Nurul Jadid. Musyrif musyrifah is a supervisor and mentor in the learning process both in academic and specialization programs. The results of the study show that the standardization of the quality of musyrif musyrifah can be concluded, namely with musyrif musyrifah services for programs that run in ma'had aly where musyrif musyrifah become parents, supervisors, mentors as well as being a place to seek insight into the turats book. The second standardization is that it can be expressed by the quality of the musyrif musyrifah itself, both in terms of the academic quality that was carried out before becoming a ma'had aly graduate, it can also be seen from the dedication that has been carried out. So in this case, musyrif musyrifah learns as well as applies his knowledge with scientific charity and practical knowledge.